Pengaruh Penerapan Corporate Social Responsibility (CSR) dan Green Accounting Terhadap Kinerja Keuangan - Sindy Firantia Dewi; Ade Imam Muslim (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2022)
This research aims to investigate the effect of the corporate social responsibility, green accounting, and financial performance. This research is a type of quantitative research with the research method used is descriptive and verification methods. The population in this study were manufacturing companies listed on the IDX for the year 2015-2019. Total of observation was 130 data which were determined using purposive sampling method and data were analyzed using panel data. The results showed the corporate social responsibility and green accounting have a significant effect simultaneously on financial performance. Partially the implementation of corporate social responsibility have no a significance effect on financial performance, while green accounting have a negative and significant effect on financial performance. Keywords: Corporate Social Responsibility, Green Accounting, and Financial PerformanceABSTRAK Penelitian ini bertujuan untuk menginvestigasi pengaruh penerapan Corporate Social Responsibility, dan Green Accounting terhadap kinerja keuangan. Penelitian ini merupakan jenis penelitian kuantitatif dengan metode penelitian yang digunakan adalah metode deskriptif dan verifikatif. Populasi dalam penelitian ini adalah perusahaan manufaktur yang terdaftar di BEI tahun 2015-2019. Jumlah observasi sebanyak 130 data yang ditentukan dengan metode purposive sampling dan analisis data dilakukan dengan analisis data panel. Hasil penelitian menunjukkan Corporate Social Responsibility dan Green Accounting berpengaruh signifikan secara simultan terhadap kinerja keuangan. Secara parsial Corporate Social Responsibility tidak berpengaruh signifikan terhadap kinerja keuangan, sedangkan Green Accounting berpengaruh negatif dan signifikan terhadap kinerja keuangan